Comparison of Safety and Tolerability of Deutetrabenazine During Titration and Maintenance in Patients with Tardive Dyskinesia. (April 2021) - Wilhelm, Amanda; Anderson, Karen E.; Fernandez, Hubert H.; Barkay, Hadas; Chaijale, Nayla; Send, Alexander F.; Savola, Juha-Matti; Gordon, Mark Forrest
Abstract: Background: Deutetrabenazine is approved to treat tardive dyskinesia (TD) in adults and is titrated weekly by 6 mg/day, from 12 to 48 mg/day, based on dyskinesia control and tolerability. This analysis compared the safety of deutetrabenazine during titration versus maintenance. Methods: Safety was assessed during titration versus maintenance using integrated data from two 12-week placebo-controlled studies (ARM-TD and AIM-TD) and the open-label extension study. Rates were compared for overall and serious adverse events (AEs), AEs leading to discontinuation, treatment-related AEs, common AEs (≥4%), and specific AEs (parkinsonism, suicidal ideation, akathisia, restlessness). Results: In titration versus maintenance, AE rates with placebo (n=130) were: overall, 43.1% vs 25.4%; serious, 4.6% vs 2.3%; leading to discontinuation, 3.1% vs 0; treatment-related, 26.9% vs 10.0%. For placebo, common AEs during titration were somnolence, headache, nausea, fatigue, and dry mouth; none occurred during maintenance. In titration versus maintenance, AE rates in fixed-dose deutetrabenazine 12–36 mg (n=216) were: overall, 33.3–38.9% vs 22.2–29.2%; serious, 2.8–6.9% vs 0–1.4%; leading to discontinuation, 2.8–5.6% vs 0; treatment-related, 8.3–16.7% vs 8.3–13.9%. For fixed-dose deutetrabenazine, common AEs during titration were headache, diarrhea, nasopharyngitis, depression, hypertension, and dry mouth; headache was the only common AE during maintenance. In titration versus maintenance, AE rates with flexible-dose deutetrabenazine (n=168) were: overall, 49.4% vs 32.7%; serious, 3.6% vs 2.4%; leading to discontinuation, 2.4% vs 0.6%. For flexible-dose deutetrabenazine, the only common AE during titration was somnolence; none occurred during maintenance. Rates of parkinsonism, suicidal ideation, akathisia, and restlessness were low and comparable in titration and maintenance. Conclusions: Deutetrabenazine was well-tolerated, with AE rates similar to placebo during both phases; AE rates were higher during titration and decreased during maintenance. Funding: Teva Pharmaceutical Industries Ltd., Petach Tikva, Israel